Design and Analysis of a Broadband Microwave Metamaterial Absorber - Yufei Zhang; Wenrong Yang; Xiaonan Li; Guoqiang Liu (IEEE Photonics Journal, 2023)
In this article, a broadband metamaterial absorber suitable for the S, C, and X bands is designed and manufactured. The absorber is made of FR-4 substrate, resonant metal structure, lumped resistance, and metal backplate, has a unit size of 0.11λL, and a total thickness of 0.084λL. The absorption principle of the absorber is analyzed using equivalent medium theory and parametric research. The calculation results show that the absorber achieves more than 90% broadband absorption (relative bandwidth of 130%) between 2.7 GHz and 12.7 GHz, has a good polarization angle and incidence angle insensitivity, uses electromagnetic resonance to explain its absorption characteristics, and experiments confirm that the absorber has good broadband absorption. The proposed absorber has higher absorption and simpler construction than the previously described broadband absorber, and it has the potential for practical applications in EMC, radar, and electromagnetic protection.